TGF-β/Smad signaling pathway positively up-regulates the differentiation of Interleukin-9-producing CD4+ T cells in human Echinococcus granulosus infection. Issue 4 (April 2018) - Pang, Nannan; Zhang, Fengbo; Li, Shaoyu; Zhu, Yuejie; Zhang, Chuntao; An, Mengting; Wang, Hongying; Mamuti, Wulamu; Ding, Jianbing; Fan, Haining
Abstract: Objectives: Cystic echinococcosis (CE) is a zoonotic disease caused by Echinococcus granulosus (Eg) infection. Th9 cells are reported to be involved in the immune responses in CE patients. This study aims to investigate the role of TGF-β/Smad pathway in the regulation of Th9 cells in CE patients. Methods: Using Western blot analysis, flow cytometry, qPCR, immunohistochemistry, ELISA and MTT assay, we measured the expression levels of TGF-β/Smad, PU.1, IRF-4, and IL-9 in CE patients. Results: The levels of TGF-β, p-Samd3, PU.1 and IL-9 were elevated in the liver of CE patients. IL-9 and IL-9R expressions were also elevated in the infected liver tissue, and IL-9 level was positively correlated with the liver inflammation. The levels of IL-9, IL-4, TGF-β and IL-10 in the supernatant were also significantly increased after stimulating hepatic lymphocytes of CE patients with Eg antigen B. After blocking the TGF-β pathway signaling in vitro, PU.1 and IL-9 were obviously reduced. Conclusions: IL-9 may aggravate the inflammatory response in the liver of CE patients. The TGF-β/Smad signaling pathway is activated, and the signaling pathway may promote the differentiation of Th9 cells and IL-9 expression in active CE patients.